TARI SERAMPANG DUA BELAS DI SUMATERA UTARA KAJIAN ESTETIKA MELALUI PENDEKATAN MULTIKULTURALISME - Sabri Gusmail (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT Several cultural aspects are noticeably clear in human’s behavior and explicitly its manifestation in people’s culture and knowledge can be tangible in customary law, traditions believed by its group of people. Art becomes the part of a culture that exists in society can be the reflection of that region cultural values so usually, the backgrounds of attainments created are cultural activities and people’s condition in a region. Serampang Dua Belas dance in North Sumatera is one of the examples of artwork that represents local culture. This dance was created by Guru Sauti in the 1940s and recreated by its creator between 1950 until 1960. Nowadays, the existence of Serampang Dua Belas dance becomes a very popular dance North Sumatera and it also has been made as national dance in Indonesia. In North Sumatera, the popularity of Serampang Dua Belas dance has become the belonging of all ethnicities in North Sumatera, even though the backgrounds of that dance are the activity and philosophy of Malay cultural values as one of the ethnicities existed in North Sumatera. Therefore, the writer tries to study aesthetic value found in Serampang Dua Belas dance through the approach of multiculturalism. Things that become the background of this dance creation and the influences that form this dance. Keywords: Dance, Aesthetic, and Multiculturalism